A climatic relict or a long distance disperser: conservation genetics of an Arctic disjunct polyploid plant - Kvist, Laura; Aminian, Leila; Rouger, Romuald; Kreivi, Marjut; Laurila, Marika; Hyvärinen, Marko; Aspi, Jouni; Markkola, Annamari
2015